Device and method for testing stability of liquid-gas interface of super-hydrophobic material

By designing a super-hydrophobic material liquid-gas interface stability test device and using laser and light intensity sensors to measure the reflected light intensity, the problem of accurate quantitative evaluation of the liquid-gas interface stability of super-hydrophobic materials in the existing technology has been solved, and efficient stability evaluation has been achieved, providing theoretical support for the development of high-performance anti-fouling and drag-reducing materials.

CN120741261APending Publication Date: 2025-10-03CHINA SHIPBUILDING INDUSTRY CORPORATION NO725 RESEARCH INSTITUTE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510877421.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

Existing technologies make it difficult to accurately and quantitatively evaluate the stability of the liquid-gas interface of superhydrophobic materials under hydrostatic pressure, which affects the development of high-performance anti-fouling and drag-reducing materials.

Method used

A device for testing the stability of the liquid-gas interface of superhydrophobic materials is designed. Laser irradiation and an illuminance sensor are used to measure the illuminance of the reflected light. A pressure sensor is used to monitor the hydrostatic pressure. The stability of the air film on the material surface is quantitatively characterized by measuring the illuminance of the reflected light at the liquid-gas interface.

Benefits of technology

The stability evaluation of superhydrophobic materials under hydrostatic pressure is realized, providing a theoretical basis for designing highly stable superhydrophobic materials. The device has a simple structure, is easy to operate, and has high test results accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005471502210000011
    Figure HDA0005471502210000011
  • Figure HDA0005471502210000012
    Figure HDA0005471502210000012
  • Figure HDA0005471502210000013
    Figure HDA0005471502210000013
Patent Text Reader

Abstract

The invention belongs to the technical field of super-hydrophobic material underwater stability evaluation, and particularly relates to a super-hydrophobic material liquid-gas interface stability testing device and a super-hydrophobic material liquid-gas interface stability testing method. Laser is irradiated to the surface of a super-hydrophobic material by utilizing the underwater silver mirror phenomenon of the super-hydrophobic material; the stability condition of an underwater gas film of the super-hydrophobic material is explored by measuring the illumination of reflected light, the stability of the super-hydrophobic material under the hydrostatic pressure is quantitatively represented, the relation between microstructure parameters of the super-hydrophobic material and hydrostatic pressure resistance is explored, and accurate evaluation of the liquid-gas interface stability of the super-hydrophobic material under the hydrostatic pressure is achieved. A theoretical basis is provided for designing an underwater high-stability super-hydrophobic material; the device is simple in structure, the method is convenient to operate, the design is rigorous and reliable, the application range is wide, the stability of the gas layer on the surface of the super-hydrophobic material can be quantitatively represented only by measuring the reflected illuminance of a liquid-gas interface, and the error of a test result is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention belongs to the technical field of underwater stability evaluation of super-hydrophobic materials, and specifically relates to a device and method for testing the liquid-gas interface stability of super-hydrophobic materials under a simulated hydrostatic pressure environment to characterize the liquid-gas interface stability of super-hydrophobic materials and evaluate the surface air film stability. Background technology:

[0002] In 2020, the global shipping industry emitted approximately 794 million tons of CO2, accounting for approximately 3% of global carbon emissions. In 2021, the global shipping industry emitted approximately 833 million tons of CO2, a year-on-year increase of 4.9%. Ships are a significant source of greenhouse gas emissions. Based on this baseline, global shipping industry carbon emissions are projected to increase by 50-400% by 2050. To improve energy efficiency and reduce greenhouse gas emissions from the shipping industry, energy conservation and emission reduction are essential. To this end, the development of highly effective antifouling and drag-reducing materials is imperative.

[0003] In nature, lotus leaves, water chestnuts, and other plants use low-surface-energy materials and rough morphologies to trap large amounts of air on their surfaces, forming a liquid-air interface and exhibiting excellent self-cleaning and drag-reducing effects. Inspired by this, superhydrophobic materials developed similarly form a large proportion of liquid-air interfaces on their surfaces. This not only enables fluids to slip on the wall, exhibiting excellent drag reduction in laminar and turbulent flows, with drag reduction rates reaching up to 70%, but also reduces the contact area for fouling organisms and the infiltration and spreading of bioadhesive secretions, reducing the number of biofouling organisms by two orders of magnitude and effectively preventing biofouling. Therefore, this material is one of the key technologies with the greatest development potential for energy conservation and emission reduction in ships, and is of great significance for reducing ship operating costs and carbon emissions.

[0004] It is well known that "building a rough structure on the surface of a low-surface-energy material" or "modifying a low-surface-energy material on the surface of a rough structure" are two major approaches to constructing a super-hydrophobic surface. Didem et al. (Langmuir, 2000, 16, 7777-7782) used laser etching to prepare a series of regular microstructures of different sizes and shapes on a silicon substrate and modified the surface with silane to obtain a super-hydrophobic surface with a maximum contact angle exceeding 170°. Xu et al. (Applied Physics Letters, 2008, 93, 233-112) first doped polymer nanoparticles in a sol-gel and coated it on a glass surface to form a thin film. The nanoparticles in the film were then removed by high temperature to form micron-sized pits. Finally, the surface was treated with fluorination to give it a good super-hydrophobic effect and to control the movement path of droplets on the surface. The people such as Liu (Applied Surface Science, 2015,351,897-903) are modified by sol-gel and long-chain fluorosilane molecules and combine the method, and the contact angle of preparation is greater than the super-hydrophobic surface of 169 °, and droplet, water jet etc. all show extraordinary hydrophobic effect on the surface. The people such as Latthe (Journal of Materials Chemistry A, 2014,2,5548-5553) add methyltrimethoxysilane in the toluene solution of dimethylformamide, the super-hydrophobic material with micro-nano layered structure prepared after high temperature sintering, the contact angle of water droplet on super-hydrophobic material surface is 159 °. The people such as Wu Xuedong (Langmuir, 2005,21,2665-2667) orientated growth zinc oxide nanocrystals on silicon substrate, then adjust surface wetting ability with the alkyl acid of different carbon chain lengths, when alkyl acid carbon chain length is greater than 16, can obtain the super-hydrophobic surface that contact angle is greater than 150 °.

[0005] Li et al. (Journal of Materials Chemistry A, 2018, 6, 17633-17641) deposited PDMS (polydimethylsiloxane) and synthesized SiO2 nanoparticles on glass by aerosol-assisted chemical vapor deposition. The prepared translucent superhydrophobic surface has a water contact angle greater than 160° and a sliding angle less than 1°. When water droplets roll off the superhydrophobic surface, the contaminated powder will be directly carried away by the water droplets, showing good self-cleaning properties. Liu et al. (Chemical Engineering Journal, 2019, 356, 318-328) formed a shark skin groove structure on a PDMS film containing SiO2 nanoparticles, and then grafted 2-(perfluorooctyl) ethyl methacrylate polymer on the surface to form a biomimetic PDMS film with superhydrophobicity, self-healing and drag reduction. The water contact angle exceeded 150° and had good self-cleaning properties. The damaged PDMS film was immersed in dimethylformamide to obtain superhydrophobic properties. In addition, the maximum drag reduction rate of the membrane in water was 21.7%, and the drag reduction performance was excellent. Wang et al. (Chemical Research in Chinese Universities, 2018, 34, 616-621) first adhered copper foil tape to the ship model, and then immersed it in a sodium hydroxide aqueous solution containing ammonium persulfate to prepare a layered structure composed of nanowires and microspheres at room temperature. Finally, it was modified with stearic acid to form a superhydrophobic coating. In the ship model drag reduction test at different speeds, the drag reduction rate was about 16%.

[0006] The micro-nanoscale rough structure of the super-hydrophobic surface can trap air underwater, forming a liquid-gas interface. When light shines on the interface, due to the difference in refractive index between the air film and water, the interface will reflect the light like a mirror, showing a silvery-white luster, which is the "silver mirror effect". As the hydrostatic pressure increases, the air film gradually disappears, and the silver mirror phenomenon gradually weakens until it disappears. Therefore, based on this physical mechanism and utilizing the "silver mirror effect" of the liquid-gas interface, a super-hydrophobic material liquid-gas interface stability testing device and method were developed and designed. By measuring the illumination of the reflected light at the liquid-gas interface, the presence of the air film on the material surface can be accurately and quantitatively characterized, and the underwater stability of super-hydrophobic materials with different microstructures can be evaluated, providing important criteria for the quantitative mapping relationship between the key microstructural parameters of super-hydrophobic materials and resistance to hydrostatic pressure, and providing important theoretical basis and technical support for the development of high-performance anti-fouling and drag-reducing materials. Summary of the invention:

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art, develop and design a super-hydrophobic material liquid-gas interface stability testing device and method, and provide a theoretical basis for designing underwater high-stability super-hydrophobic materials.

[0008] In order to achieve the above-mentioned purpose, the main structure of a super-hydrophobic material liquid-gas interface stability testing device involved in the present invention includes a controller and a pressurizing unit, a hydrostatic pressure environment simulation unit, a laser generator, and an illuminance sensor connected thereto, wherein the controller is a programmable controller, the laser generator can generate a red laser with a diameter of 1 cm, and the measurement range of the illuminance sensor is 0-9999 lux.

[0009] The controller involved in the present invention controls the start and stop of the pressurizing unit, adjusts the air flow speed through the throttle valve to control the pressurization speed, controls the opening and closing of the laser generator through the switch, collects hydrostatic pressure data through the pressure sensor, collects the illumination data of the reflected laser through the reflected light intensity sensor, and provides power for the pressure sensor, light illumination sensor, and laser generator.

[0010] The main structure of the pressurizing unit involved in the present invention comprises a gas cylinder and a check valve connected thereto; the check valve is a one-way check valve that can prevent liquid from entering the gas cylinder.

[0011] The main structure of the hydrostatic pressure environment simulation unit involved in the present invention includes: a pressure-resistant tank and a pressure-resistant observation window and a cover plate arranged thereon, as well as a pressure sensor, a throttle valve with a flow sensor, and a pressure relief valve arranged on the cover plate; the pressure-resistant tank is a pressure-resistant cast iron tank body with a volume greater than 8L, a sample table is arranged inside, and a sealing gasket is arranged between the pressure-resistant observation window and the cover plate; the pressure-resistant observation window adopts special glass with high light transmittance and high pressure resistance, which can withstand a pressure of 3MPa, and is fixed to the side of the pressure-resistant tank by bolts; the cover plate is made of cast iron; the pressure sensor has a measuring range of 0-10MPa, and the throttle valve and the pressure relief valve are both made of brass; the length, width, and height of the sample table are 60mm, 60mm, and 20mm respectively, and a groove component with a length, width, and height of 45mm, 45mm, and 5mm respectively is arranged in the center, which can ensure the firmness of sample fixation and the simplicity of replacement.

[0012] The specific process of the method for testing the liquid-gas interface stability of a super-hydrophobic material according to the present invention is as follows:

[0013] First, place the superhydrophobic sample on the sample table at the bottom of the pressure tank, add distilled water to the pressure tank, cover it with a cover plate and secure it with bolts to ensure good sealing of the pressure tank;

[0014] Then, the laser generator and the light intensity sensor are turned on, and the relative positions of the laser generator and the light intensity sensor are adjusted so that the emitted laser is reflected by the air film on the surface of the super-hydrophobic sample and the reflected light is just reflected onto the light intensity sensor;

[0015] Finally, open the gas cylinder and control the airflow speed to 1L / min by adjusting the throttle valve. At the same time, start recording the data of the pressure sensor and the light intensity sensor. When the reading of the light intensity sensor is stable, throttle the valve and the gas cylinder in turn, open the pressure relief valve, and complete the test after the reading of the pressure sensor returns to zero. Draw a chart based on the recorded data of the pressure sensor and light intensity sensor to evaluate the stability of the underwater air film of the superhydrophobic sample.

[0016] Compared with the prior art, the present invention utilizes the silver mirror phenomenon of a super-hydrophobic material underwater, irradiates a laser onto the surface of the super-hydrophobic material, explores the stability of an underwater air film of the super-hydrophobic material by measuring the illumination of reflected light, quantitatively characterizes the stability of the super-hydrophobic material under hydrostatic pressure, explores the relationship between microstructural parameters of the super-hydrophobic material and the hydrostatic pressure resistance, achieves accurate evaluation of the stability of the liquid-gas interface of the super-hydrophobic material under hydrostatic pressure, and provides a theoretical basis for designing underwater high-stability super-hydrophobic materials. The present invention has a simple device structure, convenient method operation, rigorous and reliable design, and a wide range of applications. The stability of the air layer on the surface of the super-hydrophobic material can be quantitatively characterized only by measuring the illumination of the reflected light at the liquid-gas interface, and the error of the test result is small. Description of the drawings:

[0017] Figure 1 It is a schematic diagram of the main structural principle of the present invention.

[0018] Figure 2 This is a schematic diagram of the main structure of the present invention in use.

[0019] Figure 3 This is a schematic diagram of the main structure of the sample platform involved in the present invention.

[0020] Figure 4 This is an isometric view of the main structure of the sample table involved in the present invention.

[0021] Figure 5 This is a schematic diagram of the main structure of the groove assembly involved in the present invention.

[0022] Figure 6 This is a schematic diagram of the illumination curve of the underwater air film reflected light of the super-hydrophobic material involved in the present invention, wherein a is the groove spacing of 100 μm, b is the groove spacing of 300 μm, and c is the groove spacing of 500 μm. Specific implementation method:

[0023] The present invention will be further described below through examples with reference to the accompanying drawings.

[0024] Example 1:

[0025] The main structure of a super-hydrophobic material liquid-gas interface stability testing device involved in this embodiment is as follows Figure 1As shown, it includes a controller 1, a gas input pipeline 2, a gas delivery pipeline 3, a gas cylinder 4, a cover plate 5, a pressure tank 6, a pressure display screen 7, an illumination display screen 8, a throttle control switch 9, a laser control switch 10, an illumination control switch 11, a check valve 12, a throttle valve 13, a pressure sensor 14, a pressure relief valve 15, a pressure observation window 16 and a bolt 17; the controller 1 is connected to the gas cylinder 4 and the pressure tank 6 with the cover plate 5 through the gas input pipeline 2 and the gas delivery pipeline 3 respectively, and the controller 1 has at least There are a pressure display screen 7, an illumination display screen 8, a throttle control switch 9, a laser control switch 10 and an illumination control switch 11. A check valve 12 is provided on the gas input pipe 2, and a throttle valve 13 is provided between the gas delivery pipe 3 and the pressure tank 6. The cover plate 5 is provided on the top of the pressure tank 6, and is also provided with a pressure sensor 14 and a pressure relief valve 15 extending into the interior of the pressure tank 6. A pressure observation window 16 is provided on the side of the pressure tank 6, which is connected to the cover plate 5 and the pressure observation window 16 respectively by bolts 17;

[0026] Among them, the gas input pipeline 2, the gas cylinder 4 and the check valve 12 cooperate to form a pressurizing unit, and the cover plate 5, the pressure tank 6, the throttle valve 13, the pressure sensor 14, the pressure relief valve 15, the pressure observation window 16 and the bolt 17 cooperate to form a hydrostatic pressure environment simulation unit.

[0027] A sealing gasket is provided between the cover plate 5 and the pressure tank 6 in this embodiment to ensure good air tightness;

[0028] The pressure display screen 7 displays the pressure of the gas input from the gas cylinder 4 into the controller 1;

[0029] The throttle control switch 9 controls the start and stop of the throttle valve 12;

[0030] The laser control switch 10 controls the start and stop of the laser generator 18;

[0031] The light intensity control switch 11 controls the start and stop of the light intensity sensor 19;

[0032] The check valve 12 is a one-way check valve;

[0033] The throttle valve 13 is equipped with a flow sensor to control the intake speed;

[0034] The pressure sensor 14 monitors the internal hydrostatic pressure of the pressure tank 6 .

[0035] The present embodiment involves a method for testing the liquid-gas interface stability of a super-hydrophobic material based on a super-hydrophobic material liquid-gas interface stability testing device. The specific process is as follows:

[0036] First, if Figure 2As shown, a laser generator 18 and an illumination sensor 19 connected to the controller 1 are placed on both sides of the pressure tank 6, respectively. A sample table 20 is placed at the bottom center of the pressure tank 6. A super-hydrophobic material is provided in the groove of the groove assembly 21 on the sample table 20, so that the bottoms of the laser generator 18, the illumination sensor 19 and the sample table 20 are on the same horizontal line.

[0037] Then, distilled water is added to the pressure tank 6, the cover plate 5 is covered and fixed with bolts 17, the laser generator 18 and the illumination sensor 19 are turned on respectively by the laser control switch 10 and the illumination control switch 11, the positions of the laser generator 18 and the illumination sensor 19 are adjusted to ensure that the laser is reflected by the air layer on the surface of the super-hydrophobic material and the reflected light just reaches the illumination sensor 19;

[0038] Finally, open the gas cylinder 4 and control the airflow speed through the throttle valve 13. At the same time, start recording the readings of the pressure sensor 14, the pressure display screen 7, and the illuminance display screen 8. When the reading of the illuminance sensor 19 stabilizes, close the throttle valve 13 and the gas cylinder 4 in turn, open the pressure relief valve 14, and complete the test after the readings of the pressure sensor 14 and the pressure display screen 7 return to zero.

[0039] like Figure 3-4 As shown, the length, width and height of the sample table 20 are 60 mm, 60 mm and 20 mm respectively, and the groove assembly 21 can ensure the stable placement and easy replacement of the sample, and its length, width and height are 45 mm, 45 mm and 5 mm respectively.

[0040] Example 2:

[0041] The specific process of the method for testing the liquid-gas interface stability of super-hydrophobic materials involved in this embodiment is the same as that of Example 1, and the groove component 21 used is as follows: Figure 5 As shown in FIG, the depth (H) is 150 μm, the width (D) is 80 μm, and the spacing (W) between the grooves is 100, 300, and 500 μm, respectively. The surface of the groove component 21 is uniformly sprayed with a layer of super-hydrophobic material and then placed on the sample table 20 for testing. The results of the observed changes in the reflected light illumination of the air film on the surface of the super-hydrophobic material as the pressure increases are shown in FIG. Figure 6 As shown:

[0042] When the groove spacing is 500μm, the superhydrophobic material is in a non-wetting state under a hydrostatic pressure of 0-0.16MPa, and the air film remains intact. Under a hydrostatic pressure of 0.16-0.36MPa, the surface of the superhydrophobic material gradually becomes wetted, and the integrity of the air film is destroyed. Under a hydrostatic pressure of 0.36MPa, the surface of the superhydrophobic material is completely wetted, and the air film completely disappears.

[0043] When the groove spacing is 300 μm, the surface of the superhydrophobic material is completely wetted under a hydrostatic pressure of 0.24 MPa, and the air film completely disappears;

[0044] When the groove spacing is 100 μm, the surface of the superhydrophobic material is completely wetted under a hydrostatic pressure of 0.12 MPa;

[0045] It can be seen from this that when the groove depth and width of the superhydrophobic material are fixed, the hydrostatic pressure resistance of the surface air film improves as the groove spacing increases. Therefore, for grooved superhydrophobic materials, the groove spacing is an important factor affecting the stability of its underwater air film. Increasing the groove spacing helps to improve the hydrostatic pressure resistance of the superhydrophobic material, providing a theoretical basis for the design of highly stable underwater superhydrophobic materials.

Claims

1. A super-hydrophobic material liquid-gas interface stability testing device, characterized in that: The main structure includes a controller and a pressurizing unit, a hydrostatic pressure environment simulation unit, a laser generator, and an illuminance sensor connected thereto. The bottoms of the laser generator, the illuminance sensor, and the sample table in the hydrostatic pressure environment simulation unit are on the same horizontal line.

2. A super-hydrophobic material liquid-gas interface stability testing device according to claim 1, characterized in that, The controller is a programmable controller that controls the start and stop of the pressurization unit, adjusts the air flow speed through the throttle valve to control the pressurization speed, controls the opening and closing of the laser generator through the switch, collects hydrostatic pressure data through the pressure sensor, collects the illumination data of the reflected laser through the reflected light intensity sensor, and provides power for the pressure sensor, light intensity sensor, and laser generator.

3. A super-hydrophobic material liquid-gas interface stability testing device according to claim 2, characterized in that, The main structure of the pressurizing unit includes a gas cylinder and a check valve connected thereto.

4. A super-hydrophobic material liquid-gas interface stability testing device according to claim 3, characterized in that, The main structure of the hydrostatic pressure environment simulation unit includes a pressure tank and a pressure-resistant observation window and a cover plate arranged thereon, as well as a pressure sensor, a throttle valve with a flow sensor, and a pressure relief valve arranged on the cover plate.

5. A super-hydrophobic material liquid-gas interface stability testing device according to claim 4, characterized in that, The laser generator can generate red laser with a diameter of 1 cm; The measurement range of the light sensor is 0-9999lux; The check valve is a one-way check valve; The pressure tank is a pressure-resistant cast iron tank with a volume greater than 8L. It is equipped with a sample table inside and a sealing gasket between the cover plate. The pressure-resistant observation window can withstand a pressure of 3MPa and is fixed to the side of the pressure tank by bolts; The cover is made of cast iron; The measuring range of the pressure sensor is 0-10MPa; The throttle valve and pressure relief valve are made of brass; The length, width and height of the sample table are 60 mm, 60 mm and 20 mm respectively, and a groove component with a length, width and height of 45 mm, 45 mm and 5 mm respectively is set in the center.

6. A super-hydrophobic material liquid-gas interface stability testing device according to claim 5, characterized in that, The specific process of use is as follows: First, place the superhydrophobic sample on the sample table at the bottom of the pressure tank, add distilled water to the pressure tank, cover it with a cover plate and secure it with bolts; Then, the laser generator and the light intensity sensor are turned on, and the relative positions of the laser generator and the light intensity sensor are adjusted so that the emitted laser is reflected by the air film on the surface of the super-hydrophobic sample and the reflected light is just reflected onto the light intensity sensor; Finally, open the gas cylinder and control the airflow speed by adjusting the throttle valve. At the same time, record the data of the pressure sensor and the light intensity sensor. When the reading of the light intensity sensor is stable, throttle the valve and the gas cylinder in turn, open the pressure relief valve, and complete the test after the reading of the pressure sensor returns to zero. Draw a chart based on the recorded data of the pressure sensor and light intensity sensor to evaluate the stability of the underwater air film of the superhydrophobic sample.

Citation Information

Cited By

  • A testing device and method for testing the erosion corrosion stability of superhydrophobic coatings

    CN122487162A